High-Level Synthesis Algorithm for Continuous-Flow Microfiuidic Biochips Under Device Volume Constraints - Chen, Zhengyang; Pan, Youlin; Chen, Zhen; Liu, Genggeng (2023 International Conference on Computer Science and Automation Technology (CSAT), 2023)
Continuous-flow microfluidic biochips (CFMBs) can precisely manipulate microfluids for bioassays. In order to enhance the efficiency of bioassays, it is imperative to carefully consider operation scheduling and device binding schemes. The existing work has considered device volume constraints at high-level synthesis to meet the actual fluid transport requirements of the CFMBs. However, this work is based on integer linear programming, which has a high algorithmic complexity and makes it difficult to meet the large-scale integration requirements of CFMBs. Therefore, a fast high-level synthesis algorithm based on a discrete particle swarm algorithm under device volume constraint is proposed. We propose a particle encoding scheme based on the operation priorities and the device binding scheme. In addition, the corresponding particle initialization method and update strategy are proposed to satisfy the device volume constraint. The experimental results show that the proposed algorithm can obtain high-level synthesis results in a short time.